Improving Citizen Satisfaction Index on Educational Study Program - Hermawan, Hermawan; Cahyasari, Erlita; Eko Wahyudi, Lestari (Jurnal Ilmiah Administrasi Publik, 2020)
This paper focus on the improvement on the quality of public services needs to be carried out sustainably, so that a periodic evaluation of public service delivery is needed. The government in the last decade has attempted to formulate an evaluation framework for public services delivery. This is proven from changes in regulations that dynamically follow the development needs. This research focuses on customer satisfaction in perceiving the service. The results show that there are several services that need to be improved.